Benefits of Curl Catheter for continuous interscalene block on postoperative pain scores and reduction of dislocation rate during physiotherapy - Lim, Seng Fatt; Abdul Ghani, Muhamad Rasydan; Mansor, Khairul Anam; Borhan, Muhammad Salman (Publisher Kugler Publications P.O. Box 20538 1001 NM Amsterdam The Netherlands info@kuglerpublications.com www.kuglerpublications.com Published for Malaysian Society of Anaesthesiologists and College of Anaesthesiologists., 2022)
This case is about the employment of curl interscalene catheter which is rarely documented in local setting. A 35-year-old gentleman with bone cyst of right humerus underwent manipulation under anaesthesia, ultrasound guided biopsy, extended bone curettage and bone grafting of right humerus in the beach chair position. A postoperative interscalene nerve block consisting of 8ml Chirocaine 0.25% was given, followed by placement of interscalene nerve curl catheter using 100mm SonoLong Curl Echo 18G with 50cm catheter under direct ultrasound guidance while patient was under general anaesthesia. The purpose of the interscalene nerve curl catheter was to facilitate physiotherapy of right shoulder by providing analgesia. Self limiting Horner’s Syndrome developed with bolus 8ml Chirocaine 0.25% over 10 minutes,however it resolved with a lower dose of 5ml Chirocaine 0.25% over 15 minutes. The curl catheter was placed in the patient for a duration of 5 days and no other catheter related complication occurred. 5 days of physiotherapy with low pain scores was achieved. After 5 days, the catheter was removed. In the use of straight catheter, there is a risk of catheter tip migration regardless of anterior or posterior approach and whether there are changes at the skin markings. In patients with catheter migration, worse pain scores were reported.